Themes and theories of the insider treading provisions of the 2004 securities services act - Adams, Morgan (Department of Commercial Law, 2024)
According to Blackman et al, ‘insider trading’ initially referred ‘to the sale and purchase of a company’s shares, debentures or other securities by persons connected or associated with the company (the ‘insiders’), who are in possession of confidential, ‘price-sensitive’ information…gained as a result of that association and not available to (other) shareholders or to the general public.’1 The practice of insider trading was first made illegal in South Africa with the introduction of s 233 of the Companies Act 61 of 1973. By the criminalising of insider trading, the conduct of an insider trader has been classified as a wrong against society.2 At present, the relevant provisions of the Securities Services Act of 2004 regulate such practices.3 The Act has repealed the Insider Trading Act 135 of 1998, which had previously governed criminal and civil liability in terms of the offence. The insider trading provisions of the Act form part of corporate governance regulations, which are aimed at improving the efficiency of financial markets.